Physiological responses to cold water immersion following cycling in the heat - Halson, S. L.; Quod, M. J.; Martin, D. T.; Gardner, A. S.; Ebert, T. R.; Laursen, P. B. (International Journal of Sports Physiology and Performance, 2008)
Cold water immersion (CWI) has become a popular means of enhancing recovery from various forms of exercise. However, there is minimal scientific information on the physiological effects of CWI following cycling in the heat. Purpose: To examine the safety and acute thermoregulatory, cardiovascular, metabolic, endocrine, and inflammatory responses to CWI following cycling in the heat. Methods: Eleven male endurance trained cyclists completed two simulated ~40-min time trials at 34.3 ± 1.1°C. All subjects completed both a CWI trial (11.5°C for 60 s repeated three times) and a control condition (CONT; passive recovery in 24.2 ± 1.8°C) in a randomized cross-over design. Capillary blood samples were assayed for lactate, glucose, pH, and blood gases. Venous blood samples were assayed for catecholamines, cortisol, testosterone, creatine kinase, C-reactive protein, IL-6, and IGF-1 on 7 of the 11 subjects. Heart rate (HR), rectal (Tre), and skin temperatures (Tsk) were measured throughout recovery. Results: CWI elicited a significantly lower HR (CWI: ?116 ± 9 bpm vs. CONT: ?106 ± 4 bpm; P = .02), Tre (CWI: ?1.99 ± 0.50°C vs. CONT: ?1.49 ± 0.50°C; P = .01) and Tsk. However, all other measures were not significantly different between conditions. All participants subjectively reported enhanced sensations of recovery following CWI. Conclusion: CWI did not result in hypothermia and can be considered safe following high intensity cycling in the heat, using the above protocol. CWI significantly reduced heart rate and core temperature; however, all other metabolic and endocrine markers were not affected by CWI.